A cost-effective protocol for single-cell RNA sequencing of human skin - Khoshbakht, Saba; Albayrak, Özgür; Tiryaki, Ergün; Ağcaoğlu, Orhan; Öktem, Ayşe; Pınar Sun, Gizem; Er Gülbezer, Elif; Ertekin, Sümeyre Seda; Boyvat, Ayşe; Vural, Atay; Vural, Seçil (Frontiers in Immunology, 2024)
Single-cell RNA sequencing (scRNAseq) and flow cytometry studies in skin are methodologically complex and expensive, limiting their accessibility to researchers worldwide. Ideally, RNA and protein-based analyses should be used complementarily on the same lesion to obtain more comprehensive information. However, existing protocols typically focus on either scRNAseq or flow cytometry analysis of healthy skin. In this paper, we introduce a novel protocol for scRNAseq analysis of immune cells in human skin that reduces costs by 2-4 times compared to existing protocols. Additionally, we provide detailed instructions for concurrent flow cytometry analysis from the same sample, outlining the necessary adaptations for analyzing both healthy and inflamed skin specimens. We explain a label-free sample multiplexing strategy that allows for the analysis of multiple samples and the essential demultiplexing steps. This strategy mitigates technical batch effects and reduces experimental costs. Furthermore, we demonstrate the impact of varying enzymatic incubation durations (1, 3, and 16 hours, with and without enzyme P) on flow cytometry results. In conclusion, we believe that the protocol presented in this article will make scRNAseq and flow cytometry analysis of skin samples more accessible to researchers new to these techniques.